claudia122752
since: 2017-11-14 02:17:00
Age: 33
About myself:
Profiles:
Asked questions: 3
Gave the right answers: 13
Points: 51
Best answer: 3

Questions on other subjects:

Mathematics, 29.10.2020, aronhaile
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
2 more answers
Biology, 29.10.2020, peno211
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
2 more answers
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
2 more answers
Mathematics, 29.10.2020, Maria3737
yeah nah yeah nahStep-by-step explanation:yeah nah yeah nah...Read More
1 more answers
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
3 more answers
Biology, 29.10.2020, swelch2010
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
2 more answers
Arts, 29.10.2020, kenz70
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
2 more answers
History, 29.10.2020, lol15arec001
TRUEStep-by-step explanation:To solve for the equation, we need to use formula y - ya = m(x - xA)y- 3 = -2 (x - 2)y - 3 = -2x + 4y = -2x + 4 + 3y = -2x + 7-2x - y + 7 = 0y = -2x +...Read More
2 more answers